Economic Policies to Control Downturn (International Journal of Scientific Research and Management (IJSRM), 2015)
Possibly, we all as an individual or as a company by one way or another in the country or around the world certainly experienced the recent global downturn. Downturn is frustrating time for businesses where revenues drop, costs seem to be unmanageable and the bottom line becomes bottomless. Normally business leaders tend to focus on revenue growth during normal and boom times while during slowdown and downturn they focus on cost management to cut or control the cost. Actual recession now appears to be over or is at least coming to an end, according to most fiscal authorities. Having survived the economic meltdown it might not yet be the moment to celebrate, it should be a time to look ahead and plan for a future in a stable economic climate. This paper put emphasize on analyzing different approaches to counter downturn.